Evaluating the Architectural Features of the Different Migrant Residences in Sabon Gari Township Zaria - Sadauki, Abdullahi; Hamza Babangida, Muhammad; Lawal Sagada, Musa; Mustapha Gwadabe, Muhammad; Sani-Katsina, Halima; Abdullah Adam, Isa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The concept of migrant and migration were defined by several field of studies within their own context, for instance, Geographers and sociologists have studied migration mostly, classify migrants as people who relocate their domicile within the same country for economic, social and political reasons. Migration cannot be discussed without discussing colonisation and therefore one of the remaining landmarks of colonisation in African continent are the introduction of urban centres which are different from the existing ancient towns and cities. Exclusion of architectural typology in architectural discourse will be addressed by assessing the architectural features and cultural diversity through documentation of different migrant houses. The qualitative method used include case study, survey, physical observation, interview with stakeholders, obtaining drawings/photographs. In addition, the investigation include survey, and assessment of the various sections of Sabon Gari Township in terms of the socio-cultural expressions of its architectural spaces and its surroundings. Purposive sampling was used and this is because of the character of the house, The sample size is drawn from the total number of houses in the study area. but twenty-five (25) houses were chosen. The township was planned by the colonial administration and it was in grid iron pattern with enough set back at the frontage of the house facing the road and is used for ceremonies. most of the houses visited are in “L” shaped whereby the building is on one side and kitchen and toilet are at extreme end of the house. It was observed and documented the houses in the township were hipped-roofed with one case of dormer window and also houses with chimneys were found. Verandahs and Balconies are important to the overall visual character of almost any building in Sabon Gari colonial township. The verandah usually served for relaxation with family members and guest. It was observed that the doors and windows in the houses were made up timber casement with vent above them. some of the houses in the study area used laterite stone as a means of finishes and decoration, while on the other hand some used plaster impression as means of design and decoration in the front facade of the building as recess on the plaster and cornice. By recognizing the role of culture in shaping architectural practices and fostering dialogue between migrant groups and the broader society, policymakers, planners, and architects can promote inclusive, sustainable, and culturally responsive approaches to housing provision and urban development.